2015
DOI: 10.1007/s11999-015-4428-1
|View full text |Cite
|
Sign up to set email alerts
|

Do Alumina Matrix Composite Bearings Decrease Hip Noises and Bearing Fractures at a Minimum of 5 Years After THA?

Abstract: Background Ceramic-on-ceramic bearing couples are theoretically attractive in total hip arthroplasty (THA) because of low wear, but concerns regarding ceramic fracture and squeaking have arisen. Improved material properties of newer alumina matrix composite (AMC) materials, known as Delta ceramics, may reduce these risks. In addition, the use of thinner liners and larger femoral heads may be helpful clinically to lower the rate of dislocation. However, limited short-term clinical results are available and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 37 publications
2
22
0
1
Order By: Relevance
“…An early attempt at a ceramic-on-ceramic resurfacing implant resulted in fracture in all cases [25] and was abandoned. However, the newest generation of delta ceramics are more fracture resistant [4,16] and could potentially be used for a resurfacing head and acetabulum.…”
Section: Methodsmentioning
confidence: 99%
“…An early attempt at a ceramic-on-ceramic resurfacing implant resulted in fracture in all cases [25] and was abandoned. However, the newest generation of delta ceramics are more fracture resistant [4,16] and could potentially be used for a resurfacing head and acetabulum.…”
Section: Methodsmentioning
confidence: 99%
“…CoC bearings have had mixed results throughout the literature, with early generations experiencing issues with ceramic fracture and squeaking [1]. The newest generation of ceramics exhibit an exceedingly low fracture risk [2,3], yet the squeaking hip continues to be an issue [4]. Ranawat et al reported 10.7 % of patients with CoC hips complained of audible squeaking [5].…”
Section: Bearing Options In Total Hip Arthroplastymentioning
confidence: 99%
“…The rate of ceramic breakage has diminished with the introduction of better components and is currently estimated to be below one in 5000 [1,20,28]. However, with more frequent use of ceramics, other concerns such as squeaking have emerged with a frequency of 0.5% to 20% [2,5,6,18,27]. All these limitations expose CoC THAs to reoperation with the 10-year survival rate ranging from 62% to 97% [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%